Intervensi Konseling dan SMS Reminder untuk Meningkatkan Kepatuhan Pengobatan Pasien Tuberkulosis Paru - Trisnawati, Dwiyana; Samiasih, Amin; Armiyati, Yunie (FORIKES, 2024)
Pulmonary tuberculosis is a contagious infection that requires routine and long-term treatment, with optimal treatment it will have an impact on the patient's compliance with taking good medication. Counseling and SMS Reminder interventions for pulmonary tuberculosis patients with treatment can solve the problem of non-compliance with treatment. The aim of this study was to determine the relationship between counseling and SMS Reminder interventions and medication adherence in pulmonary tuberculosis patients. This study was a systematic review implemented based on Preferred Reporting Items for Systematic Reviews and Meta-Analyzes (PRISMA). The databases used were Google Scolar, Proquest and Pubmed; limited to publications in the last 5 years, namely 2018 to 2022. The keywords used were